Phosphinines versus mesoionic carbenes: a comparison of structurally related ligands in Au(i)-catalysis. Issue 1 (29th November 2016) - Rigo, Massimo; Hettmanczyk, Lara; Heutz, Frank J. L.; Hohloch, Stephan; Lutz, Martin; Sarkar, Biprajit; Müller, Christian
Abstract : Gold(i ) complexes based on a 2, 4, 6-triarylphosphinine and a mesoionic carbene derivative have been prepared and applied in catalytic reactions. Abstract : Gold(i ) complexes based on a 2, 4, 6-triarylphosphinine and a mesoionic carbene derivative have been prepared and characterized crystallographically. Although structurally related, both heterocycles differ significantly in their donor/acceptor properties. These opposed electronic characteristics have been exploited in Au(i )-catalyzed cycloisomerization reactions. For the conversion of the standard substrate dimethyl 2-(3-methylbut-2-enyl)-2-(prop-2-ynyl)malonate the results obtained for both Au-catalysts were found to be very similar and comparable to the ones reported in the literature for other carbene- or phosphorus(iii )-based Au(i )-complexes. In contrast, a clear difference between the catalytic systems was found for the cycloisomerization of the more challenging substrate N -2-propyn-1-ylbenzamide. A combination of the phosphinine-based complex and [AgSbF6 ] or [Cu(OTf)2 ] leads to a catalytic species, which is more active than the mesoionic carbene-based coordination compound. We attribute these differences to the stronger π-accepting ability of phosphinines in comparison to mesoionic carbenes. The here presented results show for the first time that phosphinines can be used efficiently as π-accepting ligands in Au(i )-catalyzed cycloisomerization reactions.